Public-Private Partnership model to link mobile clinical veterinary services with woreda (county) veterinary offices in Ethiopia - CGIAR Research Program on Livestock (2019)
Regional task forces to discuss interactions of public and private veterinary service providers were established in 3 regions in Ethiopia (Oromia, Amhara and Somali regions). In all 3 regions, new modalities of public-private partnerships were discussed, consensus on roles reached and authorizations given. Awaiting piloting.